CLIMATE PHENOMENON OF LA NIÃ±A AND EL NIÃ±O ADVANCES ON VARIATION IN SEA WATER LEVEL OF LEMBEH STRAIT AND SANGIHE WATERS - ., Riyadi; Tarumingkeng, Adri A; Djamaluddin, Rignolda; Mamuaya, Gybert E (AQUATIC SCIENCE & MANAGEMENT, 2013)
Coastal Waters of Lembeh Strait characterizes by small waves and bathymetry undulation. While Sangihe waters have big waves, coastal bays with gently sloping beaches and flawless beaches that are generally steep headlands or cliffs on the shoreline. Differences in these two characters are interesting to watch, especially the value of the Mean Sea Level (MSL). The Least square method is the method of calculating the tidal harmonic constants which are the amplitude and phase lag. Formzahl number calculation is used to determine the type of the tidal in these two waters. The Formzahl numbers of these two waters ranged from 0.26-1.5, so there was no difference in the tidal type. The type of tidal of these two waters was catagorised as Mixed Tide Prevailing Semidiurnal, which is generally in eastern Indonesia waters. Comparison of the fluctuation of Mean Sea Level (MSL) in Lembeh Strait waters in normal climatic conditions, lanina and elnino showed the difference in height. In elnino condition, the MSL value was 87 mm lower (5.9%) than in normal operating condition (1387 mm), and in lanina condition, the average of MSL was higher 51 mm (3.46%) of the normal condition (1525 mm). While in normal climatic conditions, the MSL was 1474 mm© Perairan laut di Selat Lembeh mempunyai karakteristik gelombang kecil dan batimetri berundulasi.  Sedangkan di perairan Sangihe memiliki gelombang besar, pantai teluk berparas pantai landai dan pantai tanjung yang umumnya terjal atau bertebing pada garis pantai. Perbedaan dua karakter ini menjadi hal yang menarik untuk diamati, terutama muka air laut rerata (MLR). Metode least square adalah metode perhitungan pasang surut yang digunakan untuk menghitung konstanta harmonik yaitu amplitude dan kelambatan fase. Dengan perhitungan bilangan Formzahl akan mengetahui tipe pasang surut di kedua perairan tersebut. Diperoleh bilangan Formzahl perairan tersebut berkisar antara 0,26-1,5, sehingga tidak ada perbedaan tipe pasang surutnya. Tipe pasang surut antara kedua perairan ini adalah tipe pasang surut campuran condong ke harian ganda. Pasang surut jenis ini banyak terdapat di perairan Indonesia bagian timur.  Perbandingan fluktuasi muka laut rerata (MLR) di perairan Selat Lembeh pada kondisi iklim normal, El Niño dan La Niña menunjukkan perbedaan ketinggian. Di mana pada kondisi El Niño mempunyai muka laut rerata (MLR) lebih rendah 87 mm (5,9%) dari kondisi normalnya yaitu 1387 mm dan pada kondisi La Niña mempunyai muka laut rerata (MLR) lebih tinggi 51 mm (3,46%) dari kondisi normalnya yaitu 1525 mm. Sedangkan pada kondisi iklim normal muka laut rerata (MLR) adalah 1474 mm©